Environmental gradients across the geographic range of Puya spathacea (Bromeliaceae) - LIDIA R. SCRIVANTI; EMANUEL FUENTES; FEDERICO O. ROBBIATI; MARÍA J. NORES (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Scrivanti LR, Fuentes E, Robbiati FO, Nores MJ. 2026. Environmental gradients across the geographic range of Puya spathacea (Bromeliaceae). Biodiversitas 27 (6): d270611. https://doi.org/10.13057/biodiv/d270611. Puya spathacea is a terrestrial bromeliad native to northwestern Argentina and southern Bolivia, distributed across montane environments. This study evaluated spatial segregation and environmental variation of occurrence records, classified into central, intermediate, and peripheral zones based on their distance from the centroid of the species' range. We assessed spatial structure, analyzed altitudinal and climatic variation, and evaluated the relationship between occurrences and river networks, while also estimating potential distribution and characterizing environmental space. Ecological niche models showed high internal consistency (AUC = 0.952±0.019; TSS = 0.845±0.047), identifying elevation (38%) and precipitation of the wettest month (13.8%) as the most influential predictors of habitat suitability. PCA-env analyses explained 83.4% of environmental variation across the first two axes, while niche overlap among zones was low (Schoener’s D = 0.02-0.20), indicating differentiated environmental space. Spatial autocorrelation was stronger at the margins, and occurrences were significantly closer to rivers than expected by chance, indicating a non-random spatial association with the hydrological network rather than direct evidence of habitat dependence. Overall, peripheral occurrences occupied environmentally distinct conditions characterized by greater climatic restriction and spatial structuring than central occurrences. These findings indicate that geographically structured occurrences contribute to within-range environmental differentiation and highlight the importance of considering environmental variation across species distributions when evaluating montane biodiversity. From a conservation perspective, preserving both central and peripheral occurrences may be relevant for maintaining the ecological breadth of the species